Influence of the European Union Traffic Policy on Traffic Development in Croatia - Mlinarić, Tomislav; Bukljaš, Mihaela; Švaljek, Ivan (Promet - Traffic&Transportation, 2012)
Joining the European Union is the strategic priority for theRepublic of Croatia. Croatia has always been part of the Europeaneconomic region. The success of adaptability of the Croatianindust1y, particularly of Croatian traffic, to the EuropeanUnion, will greatly depend on the possibility of establishing contractualrelations of the economic and traffic branches with theEU. Therefore, this paper considers in more detail the traffic aspectsof integration.It is a fact that the EU traffic policy is contained in the RomanAgreement (1957) whose aim was elimination of the barriersfor the flows of goods, se1vices and capital, and the integrationof the European region. Thus, it requires equal treatmentof all the traffic branches and all the carriers, freedom forthe activities of transport companies, as welT as freedom for these1vice users to choose the transport means and carriers. Thisnaturally requires maximum rationality in fi·eight flows reflectedon the financial and commercial business activities of acompany.To converge maximally with the European Union is thestrategic priority of the Republic of Croatia, and within the Croatianindus fly this will especially require the adaptation of theCroatian traffic. The basic precondition for the functioning ofthe traffic ~ystem on the European transport market is the compliancewith the rules and standards determined by the internationalconventions.